Witchcraft in Russia and Ukraine, 1000-1900 : a sourcebook - Kivelson, Valerie A. (Valerie Ann); Worobec, Christine D., 1955- (Northern Illinois University Press, an imprint of Cornell University Press, 2020)
"This book provides the first systematic overview of witchcraft laws and trials in Russia and Ukraine, combining scholarly commentary with primary source materials translated from Polish, Russian, and Ukrainian, most of which have never before been published" -- Provided by publisher.
Keywords: Witchcraft -- Russia -- History.; Witchcraft -- Ukraine -- History.; Magic -- Russia -- History.; Magic -- Ukraine -- History.; Witchcraft -- Law and legislation -- Russia.; Witchcraft -- Law and legislation -- Ukraine.; Sorcellerie -- Russie -- Histoire.; Sorcellerie -- Ukraine -- Histoire.; HISTORY / Russia & the Former Soviet Union.; Magic; Witchcraft; Witchcraft -- Law and legislation; Russia; Ukraine; witchcraft, magic, trials, laws, possession, Social Conditions, polish translation.; Electronic books.; History